2011
DOI: 10.1016/j.actbio.2010.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of biomodified dentin matrices for potential preventive and reparative therapies

Abstract: Biomodification of existing hard tissue structures, specifically tooth dentin, is an innovative approach proposed to improve the biomechanical and biochemical properties of tissue for potential preventive or reparative/regenerative therapies. The objectives of the study were to systematically characterize dentin matrices biomodified by proanthocyanidin-rich grape seed extract (GSE) and glutaraldehyde (GD). Changes to the biochemistry and biomechanical properties were assessed by several assays to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
111
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(118 citation statements)
references
References 40 publications
3
111
0
4
Order By: Relevance
“…187,188,189,190,191 Such enzymatic reactions are the basis of tissue stability, viscoelasticity and strength of collagen fibrils. 184,192 In particular, intra-molecular cross-links provide primarily biostability to the collagen molecule, while intermolecular and inter-microfibrillar cross-links enhance mechanical properties, in addition to fibril biostability. 193 Exogenous cross-linking agents have been proposed to mimic physiological cross-links.…”
Section: Cross-linkersmentioning
confidence: 99%
See 2 more Smart Citations
“…187,188,189,190,191 Such enzymatic reactions are the basis of tissue stability, viscoelasticity and strength of collagen fibrils. 184,192 In particular, intra-molecular cross-links provide primarily biostability to the collagen molecule, while intermolecular and inter-microfibrillar cross-links enhance mechanical properties, in addition to fibril biostability. 193 Exogenous cross-linking agents have been proposed to mimic physiological cross-links.…”
Section: Cross-linkersmentioning
confidence: 99%
“…195,205 Their interaction with collagen type I depends on the type of PA, chemical structure, stereochemistry pattern and concentration of these natural extracts. 206,207 PA is a natural cross-linking agent that has been widely studied in recent years due to their ability to biomodify the dentin matrix 184 and enhance its mechanical properties and resistance against biodegradation, finally favoring the resin/dentin bond strengths. 199,204 PA can interact with collagen tissue and induce non-enzymatic collagen cross-linking 193 increasing collagen stiffness and dentin bond strength by keeping the bonding stable over time.…”
Section: Cross-linkersmentioning
confidence: 99%
See 1 more Smart Citation
“…The dentin interactions with polyphenol-rich extracts of Vitis vinifera (grape) and Theobroma cacao (cocoa) seeds have been reported (Castellan et al, 2010Bedran-Russo et al, 2011), albeit with limited extract profiling. Additional potential sources of PACs were selected to expand the scope of the study and help identify the most suitable PAC sources before initiating isolation of bioactive phytoconstituents.…”
mentioning
confidence: 99%
“…It is demonstrated that PA can cause significant drops in glycosaminoglycan (GAG) content in demineralized dentin, that consequently will alter hydration pattern and molecular sieve effect in dentin. All these factors would enhance mechanical properties of resin-dentin inter-diffusion zone 51) . Furthermore, there are several reports indicating that the susceptibility of dense PA treated collagen matrix to creep rupture or cyclic fatigue rupture, would be declined after prolonged intraoral function 52,53) .…”
Section: Pa-collagen Fibers Interactionsmentioning
confidence: 99%